Are rural residents happier? A quantitative analysis of subjective wellbeing in Scotland. (April 2016) - Gilbert, Alana; Colley, Kathryn; Roberts, Deborah
Abstract: This paper uses ordered logit models to test for evidence of systematically higher levels of subjective wellbeing in rural Scotland, differentiating between remote rural and accessible rural areas. Data are drawn from the 2008/9 wave of the BHPS covering a sample of almost 2150 Scottish residents. Two alternative quantitative measures of subjective wellbeing are used in the analysis, one based on life satisfaction, the other on mental wellbeing. The results find statistically significant evidence of higher life satisfaction in remote (but not accessible) rural Scotland after having controlled for the individual characteristics of respondents. In contrast, the mental wellbeing measure is not found to vary across rural-urban space. The paper concludes by suggesting several areas for further analysis emphasising how such research could support Scottish Government policy. Highlights: There is evidence of higher life satisfaction in remote rural areas of Scotland. There is no evidence of higher life satisfaction in accessible rural areas in Scotland. Mental wellbeing was not found to vary across rural-urban space. The results confirm the value of using multiple measures of wellbeing.